Design and Analysis of a New Type of Groove Wheel Mechanism based on ADAMS - Wu Lipeng; Wang Zhenhong; Jia Wenbo; Wang Lei (Jixie chuandong)
The groove wheel mechanism has the characteristics of intermittent movement and large transmission ratio,it is widely used in the machine system of projector,machining center and packaging machine.But with the increase of the rotation ratio,the groove wheel mechanism can’t run smoothly. In order to solve this problem,on the basis of the original groove wheel mechanism,an auxiliary locking wheel is added to realize the smooth operation of the groove wheel mechanism under the large turning and stopping ratio. By using Solid Works three-dimensional software,the three-dimensional model of the groove wheel mechanism is established,combined with the virtual prototype software ADAMS,the motion simulation of the groove wheel mechanism is carried out,the stability conditions of the whole transmission process under the condition of large-turn-stop ratio are proved.